AGRICULTURAL SATELLITE IMAGE CLASSIFICATION USING AUTOMATIC COLOR EXTRACTING TECHNIQUE - Tawfeeq, Rafid (Iraqi Journal of Science, 2024)
Automatic features extraction remains an open research area in the satelliteimages classification. While many algorithms had proposed for features extraction,none of them solved the problem completely. This paper presented a new techniquefor increasing the accuracy of the classification depending on color extraction fromselected band combination image and an acceptable classification results obtainedby comparing with traditional classification technique (parallelepiped technique).